2012
DOI: 10.4212/cjhp.v65i3.1140
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Novel Vancomycin Dosing Nomogram for Achieving High-Target Trough Levels at 2 Canadian Teaching Hospitals

Abstract: Background: Recent guidelines recommend a vancomycin trough (predose) level between 15 and 20 mg/L in the treatment of invasive gram-positive infections, but most initial dosing nomograms are designed to achieve lower targets (5-15 mg/L). Clinicians need guidance about appropriate initial dosing to achieve the higher target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 15 publications
(19 reference statements)
1
21
0
Order By: Relevance
“…This may be the case for the Thalakada et al nomogram as well. The nomogram developed by Thalakada et al was designed to achieve troughs between 15 and 20 mcg/mL only, and a majority (86%) of patients included in the nomograms development had normal renal function, with serum creatinine measurements less than or equal to 1.6 mg/L [12]. It is also important to note that rounding was permitted within the Thalakada et al study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may be the case for the Thalakada et al nomogram as well. The nomogram developed by Thalakada et al was designed to achieve troughs between 15 and 20 mcg/mL only, and a majority (86%) of patients included in the nomograms development had normal renal function, with serum creatinine measurements less than or equal to 1.6 mg/L [12]. It is also important to note that rounding was permitted within the Thalakada et al study.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several dosing strategies that have been published aimed at achieving these higher trough levels, each with varying limitations [1012]. The nomogram by Kullar et al was designed to achieve troughs between 15 and 20 mcg/mL and was found to be effective in 58% of patients in which it was studied [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13] The nomogram published in North America, developed by Kullar and colleagues, was the first nomogram to target trough concentrations of 15 to 20 mg/L. 10 This prospective study did not have a control group, but it analyzed achievement of target trough concentrations and rates of nephrotoxicity within a population of patients.…”
mentioning
confidence: 99%